Reactive oxygen species modulate HIF-1 mediated PAI-1 expression: involvement of the GTPase Rac1 - Görlach, Agnes; Berchner-Pfannschmidt, Utta; Wotzlaw, Christoph; Cool, Robbert H.; Fandrey, Joachim; Acker, Helmut; Jungermann, Kurt; Kietzmann, Thomas (Thrombosis and Haemostasis, 2003)
The hypoxia-inducible transcription factor HIF-1 mediates upregulation of plasminogen activator inhibitor-1 (PAI-1) expression under hypoxia. Reactive oxygen species (ROS) have also been implicated in PAI-1 gene expression. However, the role of ROS in HIF-1-mediated regulation of PAI-1 is not clear. We therefore investigated the role of the GTPase Rac1 which modulates ROS production in the pathway leading to HIF-1 and PAI-1 induction.Overexpression of constitutively activated (RacG12V) or dominant-negative (RacT17N) Rac1 increased or decreased, respectively, ROS production. In RacG12V-expressing cells, PAI-1 mRNA levels as well as HIF-1α nuclear presence were reduced under normoxia and hypoxia whereas expression of RacT17N resulted in opposite effects. Treatment with the antioxidant pyrrolidinedithiocarbamate or coexpression of the redox factor-1 restored HIF-1 and PAI-1 promoter activity in RacG12V-cells. In contrast, NFκB activation was enhanced in RacG12V-cells, but abolished by RacT17N. Thus, these findings suggest a mechanism explaining modified fibrinolysis and tissue remodeling in an oxidized environment.
Keywords: PAI-1; Rac1; reactive oxygen species; hypoxia; fibrinolysis; thrombosis